RANCANG BANGUN APLIKASI E-DOCUMENT SEBAGAI MEDIA PENDISTRIBUSIAN PURCHASE ORDER DAN BERBASIS WEB PADA PT. IRC INOACPENYIMPANAN DATA DIGITAL - Edi Kalsid; Henri Septanto (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2023)
A Purchase Order is a document ordering goods or services from a buyer to a supplier/supplier, almost all companies have a purchasing or purchasing department where the department will issue a goods ordering document or purchase order, the purpose of this writing is to make it easier for the purchasing or purchasing department team to distribute purchase order documents or purchase orders and store these documents digitally to make it easier to find these documents at a later date. in collecting data the author uses primary data, namely data obtained, collected and processed by the researcher directly from the subject or research object, the data collection method carried out by the researcher is carried out through: observation, interviews and participant observation. The results of the research are in the form of a web-based e-document application and distribution of purchase order documents to suppliers in a digital and structured manner so that it makes it easier for both parties to send information.